2014
DOI: 10.1016/j.jppr.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-diffusion effects on MHD stagnation point flow towards a stretching sheet in a nanofluid

Abstract: Thermodiffusion effects on stagnation point flow of a nanofluid towards a stretching surface with applied magnetic field is presented. Similarity transforms are applied to reduce the equations that govern the flow to a system of nonlinear ordinary differential equations. Runge-Kutta-Fehlberg method is applied to solve the system. Results are compared with existing solutions that are special cases to our problem. Concrete graphical analysis is carried out to study the effects of different emerging parameters su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…As proposed by Maxwell [18], the effective electrical conductivity of the nanofluid can be written as:…”
Section: Governing Equationsmentioning
confidence: 99%
“…As proposed by Maxwell [18], the effective electrical conductivity of the nanofluid can be written as:…”
Section: Governing Equationsmentioning
confidence: 99%
“…They considered the concentric annulus between cold and heated elliptic cylinders by applying magnetic action. Many researchers added valuable information about this novel field of nanofluids [18][19][20][21][22][23][24][25][26][27] The present study deals with the three dimensional model of heat flow of a nanofluid in a rotating system under the action of magnetic forces. Detailed analysis of the effects of Reynolds number, magnetic parameter, Rotation parameter, Diffusive parameter, Thermophoretic and Brownian motion parameters on the velocity, temperature, concentration profiles and rate of heat transfer is provided.…”
Section: Introductionmentioning
confidence: 99%
“…Current progress in nanotechnology introduced the use of fluids mixed with nanoparticles, called as nanofluids. The use of nanofluids in industries has become of great importance due to its applications, particularly the enhancement of thermal conductivity of a fluid (Rao 2010;Eastman et al 2001;Choi et al 2001;Xie et al 2002;Xie et al 2003;Khan et al 2014). Experimental study has shown that the effect that nanoparticles have on the enhancing the thermal conductivity depends on many circumstances including the shape and size of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%